Evaluation of Iron Tablet Program Among Pregnant - Assaini Carinta Padang; Haerawati Idris (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Anemia was one of the health problems throughout the world, especially in developing countries. The purpose of this study was to evaluate the program of iron tablets among pregnant women. This study used the CIPP evaluation model approach (Context, Input, Process, and Product). The Informant selected by the purposive method. The technique of data collection was done through in-depth interviews, document review, and observation. Data analysis was done by content analysis. The results of the study showed the components of the context of the birth of the blood supplement tablet program to reduce the prevalence of anemia in pregnant women. In the input, there was no division of tasks and responsibilities of human resources involved in the iron tablet program and the limitations of extension infrastructure. In the process, there were some health center officers who have not distributed iron tablets to pregnant women who have not made Antenatal Care visits. Some midwives did not provide reported to the Community Health Centers every month. This caused the majority of regnant women were still not obedient to consuming iron tablets, and the results show that the target coverage has not been achieved.